The Intracellular Threonine of Amyloid Precursor Protein That Is Essential for Docking of Pin1 Is Dispensable for Developmental Function - Barbagallo, Alessia P. M.; Wang, Zilai; Zheng, Hui; D'Adamio, Luciano (PLOS ONE, 2011)
Background Processing of Aβ-precursor protein (APP) plays an important role in Alzheimer's Disease (AD) pathogenesis. Thr residue at amino acid 668 of the APP intracellular domain (AID) is highly conserved. When phosphorylated, this residue generates a binding site for Pin1. The interaction of APP with Pin1 has been involved in AD pathogenesis. Methodology/Principal Findings To dissect the functions of this sequence in vivo, we created an APP knock-in allele, in which Thr668 is replaced by an Ala (T668A). Doubly deficient APP/APP-like protein 2 (APLP2) mice present postnatal lethality and neuromuscular synapse defects. Previous work has shown that the APP intracellular domain is necessary for preventing early lethality and neuromuscular junctions (NMJ) defects. Crossing the T668A allele into the APLP2 knockout background showed that mutation of Thr668 does not cause a defective phenotype. Notably, the T668A mutant APP is able to bind Mint1. Conclusions/Significance Our results argue against an important role of the Thr668 residue in the essential function of APP in developmental regulation. Furthermore, they indicate that phosphorylation at this residue is not functionally involved in those APP-mediated functions that prevent (NMJ) defects and early lethality in APLP2 null mice.